NBTI effects on circuit reliability performance of 4-bit Johnson counter based on different simulation configuration / M. F. Zainudin ...[et al.] - Zainudin, M. F.; Hussin, H.; Karim, J.; Halim, A. K. (UiTM Press, 2018)
Negative-bias temperature instability (NBTI) has become a serious circuit reliability concern as technology nodes decrease to nanometer scales. This paper presents comprehensive analyses of the NBTI effect on 4-bit Johnson Counter with a 16-nm High Performance (HP) Predictive Technology Model (PTM). The threshold voltage shift and delay degradation of Johnson Counter are analyzed in the presence of NBTI degradation using a MOSRA model based on different configuration of stress measurement with different diffusion species. The threshold voltage shift for the simulation with no circuit cut-off time is higher than the simulation with circuit cut-off time. Not only that, threshold voltage shift with atomic hydrogen species also shows the highest compared to molecular hydrogen species. As a result, simulations with no circuit cut-off time with atomic hydrogen species contribute the highest NBTI degradation. The results show that the main concern of NBTI degradation impact on the circuit performance can increase the delay up to 15.31% and an average power reduction of up to 13.31% in 10-year lifetime.